Study on Trafficking in Persons and Smuggling of Migrants in the Context of the Displacement caused by the War in Ukraine - United Nations Office on Drugs; Crime (United Nations, 2025)
The war in Ukraine has resulted in millions of people being displaced internally and outside the country since February 2022. This UNODC study, launched in February 2025, examines the risks and incidence of trafficking in persons and smuggling of migrants in the context of the displacement caused by the conflict in Ukraine, and the implications for policy and practice. The research analyses the evolution of trafficking in persons and smuggling of migrants during the years 2022 to 2024, based on relevant literature, statistics, a survey in 2023 of over 1,600 Ukrainians and non-Ukrainians displaced from Ukraine and key informant interviews in Ukraine, Germany, Poland and Switzerland. The study finds that the incidence of smuggling of migrants and trafficking in persons in the context of the displacement remain relatively low as of the time of publication. The refugee response in Europe – maintaining visa-free entry for refugees from Ukraine and facilitating rapid access to temporary protection or equivalent legal residence statuses – largely prevented smuggling of migrants, in a situation where over 6.7 million people from Ukraine sought refuge abroad.